Optimalisasi Konsep Anti Korupsi dalam Tata Kelola Pemerintahan Desa Sukahurip - Inggris, Raja; Sapitri, Dewi; Cisyara, Sinta Naila; Khotimah, Iin Husnul; Hayat, Dila Fadlilah; Gustaman, Randy Fadillah (CV. Ulil Albab Corp, 2024)
Anti-corruption education needs to be introduced to village officials so that the seeds of corrupt values do not emerge. This value cultivation must be done consistently and continuously because a person's personality is not formed instantly, but through a process. Corruption cases do not only occur in the central government, but many also occur at the village level with various causal factors. There are also external influences that can cause corruption at the village level, such as pressure from certain parties, unclear policies, and legal loopholes that can be utilized by individuals. One of the most vital issues at the village government level is funding and time. Corruption of village funds committed by village heads has a negative impact on society as it can hamper development, as well as undermine good governance, and adversely affect village development and community welfare. Therefore, serious efforts are needed to prevent and eradicate corruption committed by village officials through optimizing the anti-corruption concept in Sukahurip village. The method used is descriptive qualitative method where information is obtained from interviews and in-depth observations. With the optimization of the anti-corruption concept, it is expected to minimize corruption cases in Sukahurip Village.